Knowledge, Attitudes, and Perceived Barriers to Genetics and Precision Medicine Among Rural Participants in a Large Academic Biobank: A Mixed-Methods Study - Meghan MacNeal; Nathan A. Bihlmeyer; Susanne B. Haga (Journal of Personalized Medicine, 2026)
Background/Objectives: Rural populations remain underrepresented in genomic research and may face unique barriers to accessing genetic and precision medicine services. This study evaluated knowledge, attitudes, beliefs, and perceived barriers related to genetics and precision medicine among rural participants enrolled in OneDukeGen (ODG), a large academic biobank and precision medicine research initiative. Methods: This mixed-methods study included rural ODG participants identified using U.S. Census Bureau rural classification code. Participants completed an online survey assessing genetics knowledge, attitudes toward genetic testing and precision medicine, healthcare utilization, and internet use. Semi-structured interviews were conducted with a subset of survey participants to further explore perceptions of genetics research, barriers to care, privacy concerns, and educational needs. Results: Among 10,305 ODG participants, 3268 (31.7%) were classified as rural, representing 97 of North Carolina’s 100 counties. A total of 111 rural participants completed surveys and 14 participated in qualitative interviews. Participants generally demonstrated favorable attitudes toward genetics and precision medicine despite moderate genetics knowledge scores. Most participants believed genetic testing could improve disease prevention and treatment selection, particularly for cancer care and pharmacogenomics applications. Qualitative interviews identified three major thematic domains: (1) perceived value and promise of genetics, (2) concerns regarding privacy, trust, and misuse of genetic information, and (3) barriers and facilitators to accessing genetic services. Participants generally viewed genetics research positively but expressed concerns regarding cost, insurance coverage, privacy, and genetic discrimination. Conclusions: Rural participants generally expressed positive attitudes toward genetics and precision medicine; however, substantial barriers related to cost, trust, privacy, awareness, and digital access remain. Community-engaged approaches emphasizing accessibility, provider education, and culturally appropriate communication may be critical for equitable implementation of precision medicine in rural communities.